Peningkatan Kemampuan Komunikasi Sains Siswa SD melalui Pembelajaran Argument Driven Inquiry Pendekatan Kontekstual - Nurdiana Siregar; Nurhasana Siregar (STKIP Andi Matappa Pangkep, 2022)
Communication skills are a competency that students must have from an early age. This study aims to analyze the improvement of students' science communication skills through Argument Driven Inquiry learning with an approach in presenting science learning. This research approach is classroom action with two cycles. Data on students' science communication skills were seen from observation, and qualitative descriptive data analysis techniques and presentations on increasing science communication competence. Students' communication skills showed a significant increase in each indicator, namely scientific argumentation skills, understanding of energy contexts, fluency and ability to respond to opinions. These four indicators found that the ability to respond to student opinions was still in the medium category, while the other three indicators were in the high category. Presentation of students' science communication skills from the first meeting. Second, third and fourth were 39.4%, 47.7%, 65.3%, and 76.4%.